Omega‐3 fatty acid biomarkers and subsequent depressive symptoms. (11th December 2013) - Persons, Jane E.; Robinson, Jennifer G.; Ammann, Eric M.; Coryell, William H.; Espeland, Mark A.; Harris, William S.; Manson, JoAnn E.; Fiedorowicz, Jess G.
<x xml:space="preserve">Abstract</x> Objective We sought to determine the relationship between the omega‐3 fatty acid content of red blood cell membranes (RBC), in particular docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), and baseline and new‐onset depressive symptoms in post‐menopausal women. We secondarily sought to characterize the association between dietary omega‐3 fatty acid intake and depressive symptomatology. Methods Study participants included 7086 members of the Women's Health Initiative Memory Study (aged 63–81 years) who had an assessment of RBC omega‐3 fatty acid concentrations at the baseline screening visit. Depressive symptoms at baseline and follow‐up were characterized using the Burnam eight‐item scale for depressive disorders (Center for Epidemiologic Studies Depression Scale/Diagnostic Interview Schedule short form) and secondarily additionally inferred by antidepressant medication use. Results In multivariable‐adjusted models, our primary exposure, RBC DHA + EPA, was not related to depressive symptoms by any measure at baseline or follow‐up, nor were RBC total omega‐3, DHA, or EPA (all p > 0.2). In contrast, dietary intake of omega‐3 was positively associated with depressive symptoms at baseline (adjusted odds ratio 1.082, 95% confidence interval 1.004–1.166; p = 0.04 for dietary DHA + EPA and Burnam score ≥0.06), although this generally did not persist at follow‐up. Conclusion No relationship between RBC omega‐3 levels and subsequent depressive symptoms was evident, and associations between dietary omega‐3 and depressive symptoms were variable. Biomarkers of omega‐3 status do not appear to be related to risk of new depression in post‐menopausal women. Copyright © 2013 John Wiley & Sons, Ltd.